Dynamics of State Power and Religious Authority in the Formation of Family Law: Case Study of Indonesia and Malaysia - Sari Purnamasari; Angga Prasetyo (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2021)
This research analyzes the dynamics of state power and religious authority in the formation of family law in Indonesia and Malaysia. Through a qualitative approach with case study methods, this research explores how these two countries integrate religious norms into the national legal framework, especially in the context of family law which is heavily influenced by Islamic interpretations and practices. Data was collected through in-depth interviews with key stakeholders as well as analysis of legal and policy documents. The research results show that although there are legislative efforts to increase gender equality in family law, implementation is often hampered by social norms and pressure from conservative religious groups. These findings also suggest that family law reform that supports gender equality requires strong political support and changes in social perceptions. Policy recommendations include the development of more effective monitoring mechanisms, gender equality-oriented training for legal stakeholders, as well as increasing the participation of women's groups in the policy-making process. This research contributes to the literature on family law and women's rights in Muslim-majority countries and offers insights for more inclusive and equitable family law reform.